MP-14 Antibiotics Resistance Patterns of Escherichia coli Isolated from Poultry in West Java - Aprilia Hardiati; . Safika; Fachriyan Hasmi Pasaribu (Hemera Zoa, 2018)
Most of poultry industries use antibiotics for health management program. They use them as bacterial infection treatment and disease prevention, known as antibiotic growth promotor (AGP) [1]. Now, worldwide concern is about antibiotics resistance. Monitoring programs are done by countries in the world to protect human and animal health [2]. The monitoring programs usually use indicator bacteria such as Escherichia coli [3].Many researchers studied about antibiotics resistance in Indonesia. Escherichia coli isolated from poultry has been resistance to doxycycline (25%) and gentamycin (12.5%) [4]. Seven E. coli isolated from fecal samples shown that resistance to methicillin (85.7%), penicillin G (71.4%) and 42,9% were resistance both doxycycline hydrochloride and streptomycin [5]. Start from Januari 1st 2018 Indonesian Misintry of Agricuture banned antibiotics as AGP, based on Permentan No. 14/2017. They tried to prevent the spread of antibiotics resistance. So, it is necessary to determine antibiotics resistance patterns, especially in E. coli as indicator bacteria.